o impacto da resistência ao antimonial trivalente na biologia e resistência à lise pelo complemento em Leishmania (leishmania) amazonensis - Silva, Daiana Karla Frade (2016)
The first-line drugs in Brazil for leishimaniasis treatment is the pentavalent antimonial, considered a prodrug because it is converted in trivalent (SbIII) during the treatment which presents many limitations, including the rising of the resistant parasite. Seeking to understand of these resistance effects in Leishmania (L.) amazonensis, promastigotes forms were cultured in glowing concentrations of SbIII then 2 mutants were selected, SbIII 1 and SbIII2 that gain resistance, respectively, 15,8 and 22,5 times bigger than wild cultures'. The morphological analysis show significant diferences in mutant's form and size when compared with the wild ones, once it has a long and slender cell body and with a long flagellum, while the majority mutants, with a resistance level 6,42 (SbIII 1) and 5,62 (SbIII 2) times bigger, presented a rounded cell body, with long flagellum. Curiously, when the mutants obtain a resistance level 15,8 (SbIII 1) e 22,5 (SbIII 2) times bigger, the morphological diference diminishes. The resistance phenotype to the SbIII manifested itself also in the amastigote like derived of both mutants. The SbIII 2 mutant presented a more stable profile of resistance than SbIII 1 one's when cultured in the absence of the drug, which denote diferences in the resistance mechanism. There was not observed cross-resistance to Amphotericin B. The promastigote forms of both mutants showed theirselves significantly more resistant to lysis throught the complement system, compared to the wild one's, sugesting that the parameter to the resistance to the antimonials and virulance might be correlated in Leishmania (L.) amazonensis.